Detection of reassortant avian influenza A (H11N9) virus in environmental samples from live poultry markets in China. Issue 1 (December 2016) - Zhang, Ye; Zou, Shu-Mei; Li, Xiao-Dan; Dong, Li-Bo; Bo, Hong; Gao, Rong-Bao; Wang, Da-Yan; Shu, Yue-Long
Abstract Background Avian influenza viruses have caused human infection and posed the pandemic potential. Live poultry markets are considered as a source of human infection with avian influenza viruses. Avian influenza routine surveillance of live poultry markets is taken annually in China. We isolated the 2 H11N9 influenza virus from the surveillance program. To better understand the risk caused by these new viruses, we characterize the genetic and pathogenicity of the two viruses. Methods Viral isolation was conducted with specific pathogen-free (SPF) embryonated chicken eggs. Whole genome was sequenced, and phylogenetic analysis was conducted. Results Two H11N9 viruses were identified, with all 8 segments belonging to the Eurasian lineage. The HA, NA, M, NS and PA genes were similar to virus isolates from ducks, and the NP, PB2 and PB1 gene segments were most similar to those viruses from wild birds, indicating that the H11N9 viruses might represent reassortant viruses from poultry and wild birds. The HA receptor binding preference was avian-like, and the cleavage site sequence of HA showed low pathogenic. The NA gene showed 94.6 % identity with the novel H7N9 virus that emerged in 2013. There was no drug resistance mutation in the M2 protein. The Asn30Asp and Thr215Ala substitutions in the M1 protein implied a potentially increased pathogenicity in mice. Both viruses were low-pathogenic strains, as assessed by the standards of intravenous pathogenicity index (IVPI) tests. Conclusion Two reassortant H11N9 avian influenza viruses were detected. These viruses showed low pathogenicity to chickens in the IVPI test. Public health concern caused by the reassortant H11N9 viruses should be emphasized during the future surveillance.